Modern Science and Knowledge According to Descartes (Economic and Political Thought, 2013)
The focus of this article is René Descartes’ bold claim that his methodas presented in the Discourse on Method, will revolutionize science as wellas philosophy. The author of this article reviews each chapter of the Discoursetrying to establish what exactly Descartes had in mind and if he deliveredwhat he had promised. The findings of the article are disappointing.Descartes skillfully uses rhetorical techniques to win his audience and to gainpublicity, yet in fact he proposes no more than just four rules of conductingresearch inserted in chapter II. The remaining five chapters are either looselyconnected with the main theme (chapters I and IV) or are entirely off thetopic (chapters III, V and VI). Chapter IV, probably the most famous in theDiscourse because of its cogito ergo sum principle, also has little in commonwith Descartes’ pledge. The author concludes that if there is anything worthyin the Discourse, it is its adolescent boldness and challenge to the establishmentof Descartes’ time. If, however, we take his Discourse at face value,then we must conclude that Descartes fails to fulfill his promise and engagesmainly in self-promotion.